2019
DOI: 10.1073/pnas.1817298116
|View full text |Cite
|
Sign up to set email alerts
|

Human pregnancy zone protein stabilizes misfolded proteins including preeclampsia- and Alzheimer’s-associated amyloid beta peptide

Abstract: Protein misfolding underlies the pathology of a large number of human disorders, many of which are age-related. An exception to this is preeclampsia, a leading cause of pregnancy-associated morbidity and mortality in which misfolded proteins accumulate in body fluids and the placenta. We demonstrate that pregnancy zone protein (PZP), which is dramatically elevated in maternal plasma during pregnancy, efficiently inhibits in vitro the aggregation of misfolded proteins, including the amyloid beta peptide (Aβ) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 84 publications
(120 reference statements)
1
56
0
1
Order By: Relevance
“…Cater et al found that PZP could efficiently inhibit the aggregation of misfolded proteins including amyloid beta peptide and maintain protein homeostasis during pregnancy, indicating that PZP might play a potential role in the development of preeclampsia and Alzheimer's disease. 4 Furthermore, as a powerful T cell immunosuppressant for preventing rejection of the fetal allograft during pregnancy, PZP was associated with airway infection, disease severity in bronchiectasis during chronic airway inflammation. 15 However, in the previous studies, the relationship between PZP expression and tumor, especially HCC was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cater et al found that PZP could efficiently inhibit the aggregation of misfolded proteins including amyloid beta peptide and maintain protein homeostasis during pregnancy, indicating that PZP might play a potential role in the development of preeclampsia and Alzheimer's disease. 4 Furthermore, as a powerful T cell immunosuppressant for preventing rejection of the fetal allograft during pregnancy, PZP was associated with airway infection, disease severity in bronchiectasis during chronic airway inflammation. 15 However, in the previous studies, the relationship between PZP expression and tumor, especially HCC was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of PZP in womens' blood plasma is detectable a few weeks postconception, then can reach up to 3 mg/ mL in some individuals by 30 weeks of gestation, and finally return to near zero immediately postpartum. 4 As a broad-spectrum immunosuppressant with antiproteinase activity, knockdown of PZP may fail to prevent rejection of heart allografts and increase susceptibility to viral infection in mice. 5 Furthermore, PZP may have been shown to play an important role in modulating T cell activation and IL-2 production.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that misfolded proteins accumulate in the urine, serum, and the placenta of women with PE [99][100][101][102][103][104]. Indeed, proteins are vulnerable to misfolding because of changes in genetic and environmental factors [105] (Figure 1).…”
Section: Amyloids In Pementioning
confidence: 99%
“…It was proposed that the high levels of PZP during pregnancy represent a maternal adaptation counteracting protein aggregation, for example via the formation of stable complexes between PZP and Aβ. PLZ, which is normally present as a dimer in biological fluids, is known to inhibit heat-induced protein aggregation [103] and could be a candidate for the efficient anti-aggregation chaperone similar to dimeric α2M.…”
Section: Possible Role Of the Human Pregnancy Zone Proteinmentioning
confidence: 99%
“…Some misfolded proteins have been shown to be toxic to cells and have been linked to numerous diseases including neurodegenerative diseases (most prominently AD, Parkinson's disease, and late-onset multiple sclerosis), type 2 diabetes, certain forms of heart disease, cancers, and cataracts [8][9][10]. In addition, although not related to advance age, misfolded proteins have been found to be associated with preeclampsia [11,12]. While oxidative stress and inflammation may play important roles in protein structural modifications and misfolding [13,14], it is difficult to determine the level of oxidative stress and inflammation in body fluids and link these to disease development.…”
Section: Introductionmentioning
confidence: 99%